Local Participation in Cultural Heritage Conservation : A Case Study of the Kusantarat Mahasarakham Province - ปัดสินธุ์, ทนงศักดิ์ (Journal for Developing the Social and Community, 2016)
The purposes of this research were to study and compare the local participation in cultural heritage conservation: a case study of the Kusantarat Mahasarakham Province of cognition participation and a willingness in the conservationof the cultural environment. The sample used in the study consisted of 329 household heads or representatives age 18 years and older in Kusantarat Subdistrict, Radio District, Mahasarakham, obtained using the stratified random sampling technique. The instrument for this research was a questionnaire and the statistics used in analyzing the data were percentage, mean and standard deviation. Findings of the study are as follows; (1) The people in the knowledge about artistic environment conservation at a medium level. (2) The people showed their opinions about the participation of the factors as a whole and in each of all the aspects in Kusantarat Mahasarakham Province artistic environment conservation at a low level in this order from the highest to the lowest means : coordination for the conservation of the cultural environment, consultation on the conservation of the cultural environment and compliance with environmental art and benefits from the conservation of the cultural environment in various fields. And (3) The people showed their opinions about the willingness of the factors as a whole and in each of all the aspects in Kusantarat Mahasarakham Province artistic environment conservation at a high level in this order from the side with the most top three : No pets, walking, roaming and maintaining a common public, keep clean and joint development time.